Global human exposure to urban riverine floods and storms. Issue 1 (6th July 2022) - Varis, Olli; Taka, Maija; Tortajada, Cecilia
Abstract: The world's urban population is soaring, with an increasing number of people exposed to urban natural hazards such as riverine floods and storm surges. The global quantification of their extent is, however, still blurred. The ongoing surge in high‐resolution data allows novel opportunities for quantification of hazards and exposure. Here, we provide a global spatial synthesis of urban populations' exposure to riverine floods and storm surges in 1990 and 2015. Our results reveal that, owing to rapid economic development globally in a large proportion of exposed areas, most of the exposure has shifted from low‐income to middle‐income countries. Asia dominates as a continent. The total growth of human exposure continues, suggesting that disaster risk reduction policies and implementation call for enduring effort.